Use of Aircraft Engine Type and Quantity and their Impact on Air Transport Safety - Krejsa, Tomáš; Hrdinová, Lenka; Hrdina, Filip; Němec, Vladimír (Kaunas University of Technology, 2019)
Air transport is the safest way to transport people and goods in the world. Aviation has gone through many years of technological development to ensure that transport takes place not only quickly but also safely while maintaining the highest safety criteria. Over the past 50 years, jet engines have replaced older piston and turboprop engines in passenger and cargo air transport. At the same time mostly, aircraft starting began to be produced with two engines compared to previous older models that had three or more engines. This paper deals with the analysis and investigation of the influence of the use of the engine type and its number on aircraft in relation to air disasters (air safety).
Použití typu a množství leteckého motoru a jejich dopad na bezpečnost letecké dopravy
Keywords: Air transport; engines; safety; air disaster; Letecké doprava; motory; bezpečnost; letecká katastrofa